MC1R major variants are a risk factor of sleep lines in Caucasian women. (4th March 2013) - Jdid, R.; Ezzedine, K.; Latreille, J.; Galan, P.; Hercberg, S.; Malvy, D.; Tschachler, E.; Guinot, C.
Abstract Background Sleep lines are caused by individual's sleeping positions and should be differentiated from expression wrinkles. Objective The aim of the study was to investigate possible risk factors for sleep lines on a sizeable sample of middle‐aged Caucasian women. Methods This study involved a sample of 542 French middle‐aged women (44 to 70 years old) from Paris area. Three standardized facial photographs (face and profiles) were examined independently by two dermatologists allowing the identification of sleep lines and the evaluation of the severity of several facial skin features. Possible impacts of MC1R gene polymorphisms were tested using logistic regression models. Results Sixty women (11%) had facial sleep lines and showed generally more than one sleep line. The sleep lines were often located on the forehead, along the nose, on the cheeks and under the eyes, and more rarely on the chin. As expected, the sleep lines were associated with age, and the women with sleep lines showed also more severe signs of skin ageing. After adjustment on possible confounders, the presence of two major diminished function variants of the MC1R gene was identified as a strong risk factor for sleep lines [adjusted odds ratios (AOR) (95% CI): 8.25 (2.62–25.97)]. Discussion/Conclusion The data in the literature are scarce and this study is the first to be conducted on a sizeable sample of women. Our results suggest that genetic variations of MC1R are important determinants of the development of sleep lines.